PERSONALITY QUALITIES ENHANCING ITS SECURITY AGAINST MANIPULATION - V P Sheinov (Peoples' Friendship University of Russia (RUDN University), 2016)
This article shows the extent of the problem of an individual being unprotected from the manipulation and its harm. No one is fully immune to manipulation and everyone can become a victim of manipulative actions. It is demonstrated that manipulative relationships have taken roots in modern society and there is a tendency for a wider spread. 92-95% respondents who have had negative state of mind resulting from being manipulated would like to learn how to protect themselves from manipulation. It is established that if individuals are focussed on themselves, they are less prone to being manipulated; if individuals are focussed on relationship they are more likely to be subject to manipulation. The personal characteristics helping to be immune to manipulation are shown, i.e. a rather high social intellect of an individual, their independence from people's opinions, low levels of trust and inquisitive minds. It is shown that 1) females are better protected from manipulation than males; 2) the degree of protection against manipulation does not depend on the person's age and the degree of machiavellism of their personality; 3) the individuals' assertiveness helps to protect themselves from manipulation. The representation level of this research and its results are guaranted by the number of participants (552 respondents) and the wide social representation: firemen, university teachers and students, military cadets, psychologists, retail employees.